(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2025)
Solutions to increase the accuracy of radio systems are analyzed. It is shown that invariance in a single-loop automatic control system affects its stability. Article [13] offers to apply a method for the synthesis of continuous high precision double-loop automatic control systems which are equivalent to combined systems in conditions when some values (entry useful action) can’t be measured for development of tracking systems (in particular, radio systems, where the entry useful action can’t be measured, and therefore combined control is impossible). The article considers extension of the method for the synthesis of double-loop automatic control systems to discrete systems equivalent to combined systems in an environment with simultaneous entry useful (preset) action and external disturbances and interferences. The developed method makes it possible to synthesize discrete high-precision automatic control tracking systems equivalent to combined ones in an environment with a controlled variable (entry useful action) which cannot be measured. A discrete transfer function from an error in double-loop system (5), an invariance condition (6), and a characteristic equation (8) are obtained. In this case, the numerator polynomial of the transfer function from error must have a difference of polynomials. The article demonstrates that invariance conditions (improved accuracy) can be achieved without any destabilization in the first loop. In this discrete tracking system equivalence to combined systems is achieved by two control loops and not by three loops as in the differential coupling method. A double-loop discrete automatic control system equivalent to a combined system was synthesized. A stochastic regulator was calculated and made, and the influence of this regulator on the astatism of the system (that is, on its accuracy) was analyzed. The proposed method can be used to develop discrete tracking systems (especially radio systems, where entry useful action cannot be measured due to interference), and it can be applied for laser radar tracking systems, and control systems for aircraft of various purposes.